2023
DOI: 10.3390/nu15081930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thymbra capitata (L.) Cav. on Inflammation, Senescence and Cell Migration

Abstract: Aromatic plants are reported to display pharmacological properties, including anti-aging. This work aims to disclose the anti-aging effect of the essential oil (EO) of Thymbra capitata (L.) Cav., an aromatic and medicinal plant widely used as a spice, as well as of the hydrodistillation residual water (HRW), a discarded by-product of EO hydrodistillation. The phytochemical characterization of EO and HRW was assessed by GC-MS and HPLC-PDA-ESI-MSn, respectively. The DPPH, ABTS, and FRAP assays were used to discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 187 publications
1
8
0
Order By: Relevance
“…The protein levels of the inducible nitric oxide synthase (iNOS) and IL-1β pro form (pro-IL-1β), with tubulin used as loading control, were assessed using Western blot, as previously described [61].…”
Section: Effect On Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The protein levels of the inducible nitric oxide synthase (iNOS) and IL-1β pro form (pro-IL-1β), with tubulin used as loading control, were assessed using Western blot, as previously described [61].…”
Section: Effect On Cell Viabilitymentioning
confidence: 99%
“…The effect of the extract on cell migration was investigated through the scratch wound assay according to Martinotti et al [62] with slight modifications. Briefly, after the scratch induction, NIH/3T3 fibroblasts were incubated in DMEM with 2% FBS alone with the addition of the essential oil (0.08-0.32 µL/mL) for 18 h. After image acquisition, the open area was quantified as reported by our team [61].…”
Section: Cell Migrationmentioning
confidence: 99%
“…This assumption is validated by the decrease in yH2AX, as it has been reported that phosphorylation of H2AX (yH2AX) is required for increasing p21 levels and therefore cells enter cell cycle arrest [ 91 ]. Previous studies from our group demonstrated anti-senescent properties for the essential oil and hydrodistillation residual water of T. capitata [ 24 ]; however, studies addressing the mechanisms of action underlying these effects are lacking. Certain studies have reported anti-aging/senescent effects for some of the major compounds found in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…The protein levels of the inducible nitric oxide synthase (iNOS) and IL-1β pro-form (pro-IL-1β) were assessed by Western blot, as previously described [ 24 ]. For protein separation, an electrophoretic assay was performed with 10% ( v / v ) SDS-polyacrylamide gels at 130 V during 1.5 h, at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation